"Black folk don't get no severe depression": Meanings and expressions of depression in a predominantly black urban neighborhood in Midwestern United States. (May 2016) - Alang, Sirry M.
Abstract: Discrepancies exist between how some Black populations perceive depression and how depression is conceptualized within research and clinical settings. Based on a 12-month ethnography of mental health in a predominantly Black disadvantaged urban neighborhood in Midwestern United States, the current study identifies meanings and common ways of expressing depression among African Americans. Depression was often considered a sign of weakness rather than a health problem that might need medical attention. Associated emotions like sadness and hopelessness were inconsistent with notions of strength. Common indicators of depression included classic symptoms such as hopelessness, loss of sleep, and feeling worthless. However, expressions of depression such as anger, agitation, violent behavior, and a frantic search for social interaction that are inconsistent with DSM-V criteria were also common. These findings have implications for the clinical assessment of depression and for the measurement of depression in community surveys. In addition, the context and meaning of symptoms play an important role in determining whether experiences are indicative of depression. This paper underscores that the provision of patient-centered mental health care requires a better understanding of the conceptualization of disorders within specific contexts. Highlights: Context shapes meanings of depression. Expressions of depression can be inconsistent with DSM-V criteria for depression. Assessment of depression should be consistent with perspectives of Black patients. Compliment epidemiological surveys with contextual information about symptoms.